The Strategy of the Gantar Village Government in the Management of Village Funds - Ahmad Cahyadi; Abdur Rahim (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
Village Funds have an important role in improving the economy of rural communities. Thus the utilization and allocation are effective and efficient. The purpose of the study was to determine the management of village funds according to Law Number 6 of 2014 Fiqh Siyasah (Study in Gantar Village, Gantar District, Indramayu Regency). This study uses a qualitative approach. Data collection techniques in observational research, interviews and documentation. The results of the research on the management of Gantar village funds, Gantar sub-district, Indramayu district, have been good, it can be seen from the progress of the village which is increasing rapidly. Financial management consists of: 1) Planning 2) Implementation 3) Administration 4) Reporting 5) Village financial accountability The village head as the party authorized to approve an expenditure plan.